Timing of oral feeding changes in premature infants who underwent osteopathic manipulative treatment. (April 2019) - Vismara, L.; Manzotti, A.; Tarantino, A.G.; Bianchi, G.; Nonis, A.; La Rocca, S.; Lombardi, E.; Lista, G.; Agosti, M.
Abstract: Background: The delayed transition from gavage-to-nipple feeding is one of the most significant factors that may prolong hospital length of stay (LOS). Osteopathic manipulative treatment (OMT) has been demonstrated to be effective regarding LOS reduction, but no investigations have documented its clinical validity for attaining oral feeding. Objectives: To assess OMT utility regarding the timing of oral feeding in healthy preterm infants. Design: Preliminary propensity score-matched retrospective cohort study. Setting: Data were extrapolated from the neonatal intensive care unit (NICU) of Del Ponte Hospital in Varese, Italy, during the period between March 2012 and December 2013. Interventions: Two propensity score-matched groups of healthy preterm infants aged 28 +0 to 33 +6 were compared, observing those supported with OMT until hospital discharge and control subjects. Main outcome measures: Days from birth to the attainment of oral feeding was the primary endpoint. Body weight, body length, head circumference and LOS were considered as secondary endpoints. Results: Seventy premature infants were included in the study as the control group (n = 35; body weight (BW) = 1457.9 ± 316.2 g; gestational age (GA) = 31.5 ± 1.73 wk) and the osteopathic group (n = 35; BW = 1509.6 ± 250.8 g; GA = 31.8 ± 1.64 wk). The two groups had analogous characteristics at study entry. In this cohort, we observed a significant reduction in TOF (-5.00 days; p  = 0.042) in the osteopathic group with a greater effect in very low birth weight infants. Conclusions: These data demonstrate the utility and potential efficacy of OMT for the attainment of oral feeding. Further adequately powered clinical trials are recommended.